Becoming Fully Human: The Greatest Glory of God - Chittister, Sister Joan (Rowman & Littlefield Publishers, 2005)
Drawing from the folklore and scripture of other cultures, as well as her own monastic tradition, Sister Joan Chittister develops a spirituality that understands what it means to be human and the importance of seeing others for what they truly are—sacred. Centered around twelve questions—from "What does it mean to be enlightened?" to "How is caring for the earth spiritual?"—Becoming Fully Human reveals that no matter our color, economic or social status, or religion, we are all dealing with the same human desires, fears, needs, feelings and hopes. Coming to see the heart of the other allows us to see our own, which in turn leads us to live lives dedicated to respect, holiness, balance, and peace.